Globalizing Homeopathic Education: Convergence with WHO-GTM Strategy 2025-2034 (Homoeopathy for All, 2025)
Modernizing Homoeopathy Edu cation: The WHO GTM Strategy  2025–2034 calls for regulated, cul turally sensitive education across  Traditional Medicine systems.  Despite its presence in over 100  countries, Homoeopathy lacks  consistent educational standards— highlighting the need for globally  aligned standards. Establish Global Educational  Benchmarks: Dedicated guide lines for homoeopathy will raise  educational quality, strengthen reg ulatory frameworks, and enhance  clinical credibility. These bench marks can support diverse educa tional models worldwide. Integrate Interdisciplinary &  Complementary Systems: Aligned  with Hahnemannian philosophy,  Homoeopathic curricula should  incorporate relevant knowledge  and competencies from other TM  —Ayurveda, Anthroposophy, Yoga  and Naturopathy—along with  nutrition, counselling, and mind– body therapies.  Mobilize Support from Member  States and Stakeholders : Member  states should be motivated to  include homoeopathy in health  policies, initiate global academic  dialogue, and adopt adaptable   standards that reflect cultural and  healthcare diversity. Embed Sustainability Across  Academic, Cultural & Systemic  Layers: Build resilience through  clinically relevant programs, local  engagement, and alignment with  national healthcare strategies—re specting indigenous and biomedical  knowledge and ecological values. Position India as a Global  Leader: Indian institutions should  champion innovation and global  collaboration—through tailored  programs, faculty exchange, and  knowledge-sharing—to establish  India as a homoeopathic education  and research leader.
Keywords: Modernizing; Global Educational Benchmarks; Global Leader; Traditional Medicine systems